Exotic Nuclei 2017
DOI: 10.1142/9789813226548_0034
|View full text |Cite
|
Sign up to set email alerts
|

TWO-PROTON RADIOACTIVITY OF 67Kr

Abstract: In an experiment with the BigRIPS separator at the RIKEN Nishina Center, we observed two-proton (2p) emission from 67 Kr. At the same time, no evidence for 2p emission of 59 Ge and 63 Se, two other potential candidates for this exotic radioactivity, could be observed. This observation is in line with Q value predictions which pointed to 67 Kr as being the best new candidate among the three for two-proton radioactivity. 67 Kr is only the fourth 2p ground-state emitter to be observed with a half-life of the orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The 2p decay in 19 Mg was observed with different techniques at GSI due to its much shorter half-life [7]. Finally, the very recent case of 67 Kr was reported in an experiment at RIKEN in Japan with a silicon detector telescope [8].…”
Section: Predicted Half-life For Observed 2p Radioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The 2p decay in 19 Mg was observed with different techniques at GSI due to its much shorter half-life [7]. Finally, the very recent case of 67 Kr was reported in an experiment at RIKEN in Japan with a silicon detector telescope [8].…”
Section: Predicted Half-life For Observed 2p Radioactivitymentioning
confidence: 99%
“…The emitted two protons have a small angular distribution and share the same energy. Until now, only five nuclei have been observed that can have 2p radioactivity from the ground state ( 45 Fe [2,4], 54 Zn [5], 48 Ni [6], 19 Mg [7], and 67 Kr [8]). A systematic study of 2p radioactivity with density functional theory suggests that this decay mode may not be limited to the light-and mediummass regions but a typical feature for even-Z proton-unbound isotopes, and should be observed for nuclei in the heavier-mass region [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using the invariant mass approach, the 2p decays of the 12 O [19] and 16 Ne [20] were experimentally studied. Eventually, in 2016, the French group at the fragment separator Big RIPS in RIKEN [21] observed the fourth 2p emitter, 67 Kr with a half-lifetime of a few milliseconds. Another 2p-unbound isotope 11 O has been discovered in 2019 [22].…”
Section: Introductionmentioning
confidence: 99%